2011
DOI: 10.1042/bj20100580
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 mediates PDGF stimulation of vascular smooth muscle cell migration and signalling via p130Cas

Abstract: NRP1 (neuropilin-1) is a co-receptor for members of the VEGF (vascular endothelial growth factor) family in endothelial cells, but is increasingly implicated in signalling induced by other growth factors. NRP1 is expressed in VSMCs (vascular smooth muscle cells), but its function and the mechanisms involved are poorly understood. The present study aimed to determine the role of NRP1 in the migratory response of HCASMCs (human coronary artery smooth muscle cells) to PDGF (platelet-derived growth factor), and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
115
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 25 publications
(37 reference statements)
8
115
1
Order By: Relevance
“…The different ligand families bind to different sites of NRP1; SEMA3A binding requires the first three sub-domains of NRP1 (a1, a2, and b1) while binding of VEGF-A requires the b1 and b2 domains (Gu et al, 2002;Mamluk et al, 2002). Despite reports of NRP1 interaction with PDGFs (Ball et al, 2010;Banerjee et al, 2006;Cao et al, 2010;Pellet-Many et al, 2011), a specific binding site for PDGFs in NRP1 is not known. In addition, interactions of NRP1 with PDGFRα or PDGFRβ have been suggested (Pellet-Many et al, 2015), but its potential role in PDGF-PDGFR signaling remains elusive.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The different ligand families bind to different sites of NRP1; SEMA3A binding requires the first three sub-domains of NRP1 (a1, a2, and b1) while binding of VEGF-A requires the b1 and b2 domains (Gu et al, 2002;Mamluk et al, 2002). Despite reports of NRP1 interaction with PDGFs (Ball et al, 2010;Banerjee et al, 2006;Cao et al, 2010;Pellet-Many et al, 2011), a specific binding site for PDGFs in NRP1 is not known. In addition, interactions of NRP1 with PDGFRα or PDGFRβ have been suggested (Pellet-Many et al, 2015), but its potential role in PDGF-PDGFR signaling remains elusive.…”
Section: Introductionmentioning
confidence: 92%
“…Others have reported that NRP1 can modulate PDGF-A-and PDGF-B-induced receptor signaling (Ball et al, 2010;Pellet-Many et al, 2011). However, whether these effects of NRP1 are direct or indirect remain open questions.…”
Section: Pdgf-d Induces the Interaction Of Pdgfrβ And Nrp1 In Trans Bmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that tyrosine phosphorylation of the adaptor protein p130Cas plays a key role in PDGF-BB-dependent migration of glioma cells and vascular smooth muscle cells Pellet-Many et al, 2011). DOK1 has been reported to associate with p130Cas upon stimulation of type 1 Fce receptors (FceRI) in mast cells, but the nature of this association is unclear, and the effect on p130Cas tyrosine phosphorylation was not determined (Abramson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that tyrosine phosphorylation of p130Cas (also known as BCAR1) plays a key role in the PDGF-BB-induced migration of U87 glioma cells and vascular smooth muscle cells Pellet-Many et al, 2011). Here, we investigated the role of DOK1 in PDGF-BBmediated cell motility and chemotactic p130Cas signalling in malignant glioma cells.…”
Section: Introductionmentioning
confidence: 99%